Answer:
f(x) and g(x) are inverse functions because:
f(g(x)) = x and g(f(x)) = x
Step-by-step explanation:
Two functions f(x) and g(x) are inverses if g(f(x)) = x and f(g(x)) = x.
So, f(x) and g(x) are equal to:
![\begin{gathered} f(x)=(x+5)/(2x+1) \\ g(x)=(5-x)/(2x-1) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ke5q79bxt9u4uurqc4umrgpeud8mr0y0kt.png)
Then, to find g(f(x)), we need to replace x by f(x) on the equation of g(x), so we get:
![\begin{gathered} g(f(x))=(5-f(x))/(2f(x)-1) \\ g(f(x))=(5-(x+5)/(2x+1))/(2((x+5)/(2x+1))-1) \\ g(f(x))=((5(2x+1)-(x+5))/(2x+1))/((2(x+5)-1(2x+1))/(2x+1)) \\ g(f(x))=\frac{5(2x+1)-(x+5)}{2(x+5)-(2x+1)_{}} \\ g(f(x))=(10x+5-x-5)/(2x+10-2x-1) \\ g(f(x))=(9x)/(9)=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7aesm7b9y28ffqju7msiihv1bnnvcerzwq.png)
Now, we need to verify that f(g(x)) is also equal to x, so:
![\begin{gathered} f(g(x))=(g(x)+5)/(2g(x)+1) \\ f(g(x))=((5-x)/(2x-1)+5)/(2((5-x)/(2x+1))+1) \\ f(g(x))=((5-x+5(2x-1))/(2x-1))/((2(5-x)+1(2x-1))/(2x-1)) \\ f(g(x))=((5-x)+5(2x-1))/(2(5-x)+(2x-1)) \\ f(g(x))=(5-x+10x-5)/(10-2x+2x-1) \\ f(g(x))=(9x)/(9)=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xc70uie9x5k21p8gcignh1yjgicajxbr4i.png)
Since g(f(x)) and f(g(x)) are equal to x, we can say that f(x) ad g(x) are inverse functions.